An Investigation for Heavy Metals’ Contamination in Farmers’ Fingernails: Case Study in Libya - Aiman M. Bobaker; Intisar Alakili; Elrashied E. Elkhidir; Sukiman B. Sarmani; Zaher Mundher Yaseen (Journal of Chemistry)
This study aims to assess the concentration levels of heavy metals, which are associated with health hazards: arsenic (As), cadmium (Cd), and lead (Pb) among Libyan farmers using fingernails as a biomarker. Factors that may contribute for accumulation of these toxic heavy metals in the farmers’ fingernails were also evaluated. This cross-sectional study involved 127 farmers and 25 high school teachers living in the same geographical area as the farmers (served as the control group). Fingernail samples of the participants were collected, treated, and analyzed by inductively coupled plasma mass spectrometry (ICP-MS) for As, Cd, and Pb contents after microwave acid digestion. Results of this study indicated that the concentration levels of the investigated heavy metals in fingernail samples of both participating farmers and control group were in order of Pb > Cd > As. Also, the results showed that As, Cd, and Pb levels in the farmers’ fingernails were found to be higher than in the control group by about 9-, 5-, and 2-fold, respectively. This difference for all heavy metals analyzed was found to be statistically significant P<0.05. As a conclusion, the results of this study clearly indicated that Libyan farmers have been exposed to high levels of toxic heavy metals as a result of their agricultural activities compared with the general population living in the same geographical area as farmers, which, in turn, pose a high risk to their health. Thus, toxicological, epidemiological, and clinical studies for the Libyan farmers are strongly recommended.